(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study investigates the levels of physical activity among PGT/TGT/PRT Government School Teachers in Haryana, recognizing the broader health implications associated with physical activity. Emphasizing the benefits of regular physical activity, including stress relief and increased life expectancy, the research focuses on a sample of 138 school teachers, encompassing both male and female participants from various regions in Haryana. Primary data is collected through the International Physical Activity Questionnaire (IPAQ) developed by Dr. Cuisle Forde. Utilizing descriptive statistics and graphical analysis, the study reveals a noteworthy shift in the lifestyle patterns of female teachers compared to their male counterparts. Female teachers exhibit significantly higher engagement in both moderate (73.85%) and high (10.77%) physical activities, surpassing the levels reported by male respondents (53.42% and 1.37%, respectively). These findings underscore the importance of gender-specific considerations in promoting physical activity among government school teachers and suggest potential areas for targeted interventions to enhance overall health and well-being.